Une ṭablītō syriaque orthodoxe en Érythrée datée de 1295/1296 : un témoin des « métropolites syriens » ? - Bausi, Alessandro; Desreumaux, Alain (Aethiopica, 2021)
A wooden altar tablet (ṭablītō) inscribed in Syriac, consecrated by an ‘Athanasius bishop of Ethiopia’ in 1295/1296 CE was recently documented from a church in the nearby of Asmara, in Eritrea. The note provides edition, translation, and commentary of the text, as well as a first assessment of its meaning in connection with the debated issue of the presence of Syrian prelates in Ethiopia and Eritrea at the end of the thirteenth century. The wooden tablet is the only ancient or medieval written object in Syriac script or language that has so far been found in Ethiopia or Eritrea.